2020
DOI: 10.1021/acs.energyfuels.0c00244
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Reduction of NO2 in Fixed Bed Combustion of Coal Char under Oxy–Fuel Conditions: Experimental and Density Functional Theory Analysis

Abstract: Nitrogen dioxide (NO 2 ) has been attracting a lot of attention because of its toxicity and potential in contaminating land, air, and water. However, research on NO 2 release behavior under oxy−fuel conditions is still insufficient. This paper aims to explore the formation and reduction mechanisms of NO 2 during oxy−fuel combustion of char by using both experimental and density functional theory (DFT) methods. Results showed that with the increase of temperature, the energy barrier of the NO oxidation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Each coal sample utilized weighed approximately 0.08 g with a precision of ±0.0001 g. The total gas flow rate was 2.67 L/min. Our prior research demonstrated that the gas flow rate of 2.67 L/min can mitigate the impact of external diffusion on experimental outcomes. At least three experiments per group were conducted to reduce experimental errors. Table shows the detailed experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Each coal sample utilized weighed approximately 0.08 g with a precision of ±0.0001 g. The total gas flow rate was 2.67 L/min. Our prior research demonstrated that the gas flow rate of 2.67 L/min can mitigate the impact of external diffusion on experimental outcomes. At least three experiments per group were conducted to reduce experimental errors. Table shows the detailed experimental conditions.…”
Section: Methodsmentioning
confidence: 99%